Два новых азиатских вида андрен (Hymenoptera, Andrenidae) - Осычнюк, А.З. (Вестник зоологии, 1985)
Andrena (Didonia) popovi sp. n. (S. Kazakhstan, Tadjikistan) differs from all other representatives of the subgenus Didonia by shorter glossa and dense, shortened tibial scopa; from closely related A. mucida Kriechb. female of the new species differs by labral process shape, elongated and flattened clypeus, mesonotal sculpture, green-bluish abdominal tergites of metallic tint, lack of apical bands of the tergites and black pubescence; male differs by longer 1st antennal flagellum segment, 7th, 8th sternites shape, genital armature and body colour. A. laticalcar sp. n. (Turkmenia) is similar to A. cochlearicalcar Lebedev by numerous subgeneric characters and by broad spur of the mid- and hindtibiae, female differs by facial foveae shape and position, spur shape, denser punctuation of the clypeus, mesonotum and tergites, denser and elongated tibial scopa, well developed trochanteral floccus. Type material is deposited in the Schmalhausen Institute of Zoology (Kiev) and in Zoological Institute, USSR Academy of Sciences (Leningrad).